Genetic determinants of acute asthma therapy response in children with moderate‐to‐severe asthma exacerbations. Issue 4 (15th January 2019) - Tse, Sze Man; Krajinovic, Maja; Chauhan, Bhupendrasinh F.; Zemek, Roger; Gravel, Jocelyn; Chalut, Dominic; Poonai, Naveen; Quach, Caroline; Laberge, Sophie; Ducharme, Francine M.; ,
Abstract: Background: We documented inter‐individual variability in the response to acute asthma therapy in children, attributed in part to five clinical factors (oxygen saturation, asthma severity score, virus detection, fever, symptoms between exacerbations; DOORWAY study). The contribution of genetic determinants of failure of acute asthma management have not been elucidated. Objective: We aim to determine single nucleotide polymorphisms (SNP) associated with emergency department (ED) management failure in children. Methods: A prospective cohort of 591 Caucasian children aged 1‐17 years with moderate‐to‐severe asthma managed with standardized protocol were included. We examined 53 SNPs previously associated with asthma development, phenotypes, or bronchodilator or corticosteroids response. Associations between SNPs and management failure (hospitalization, active asthma management ≥8 h in ED, or a return visit within 72 h for one of two previous criteria) were examined using logistic regression, adjusting for the five clinical predictors of management failure. Results: Four‐hundred ninety‐one subjects had complete clinical data and usable DNA samples. While controlling for clinical determinants, rs295137 in SPATS2L (OR = 1.77, 95%CI: 1.17, 2.68) was significantly associated with increased odds of ED management failure. Two SNPs in IL33 were associated with decreased odds of ED management failure: rs7037276 (OR = 0.55, 95%CI: 0.33, 0.90), and rs1342326 (OR = 0.52, 95%CI: 0.32, 0.86). The addition of these three SNPs to the clinical predictors significantly improved the model's predictive performance ( P < 0.0004). Conclusion: Three SNPs were significantly associated with ED management failure in addition to clinical predictors, contributing to inter‐individual variability. None has been previously associated with treatment response to acute asthma management.